Cancer Vaccines: Adjuvant Potency, Importance of Age, Lifestyle, and Treatments - Cuzzubbo, Stefania; Mangsbo, Sara; Nagarajan, Divya; Habra, Kinana; Pockley, Alan Graham; McArdle, Stephanie E. B. (Frontiers in Immunology, 2021)
Although the discovery and characterization of multiple tumor antigens have sparked the development of many antigen/derived cancer vaccines, many are poorly immunogenic and thus, lack clinical efficacy. Adjuvants are therefore incorporated into vaccine formulations to trigger strong and long-lasting immune responses. Adjuvants have generally been classified into two categories: those that ‘depot’ antigens (e.g. mineral salts such as aluminum hydroxide, emulsions, liposomes) and those that act as immunostimulants (Toll Like Receptor agonists, saponins, cytokines). In addition, several novel technologies using vector-based delivery of antigens have been used. Unfortunately, the immune system declines with age, a phenomenon known as immunosenescence, and this is characterized by functional changes in both innate and adaptive cellular immunity systems as well as in lymph node architecture. While many of the immune functions decline over time, others paradoxically increase. Indeed, aging is known to be associated with a low level of chronic inflammation - inflamm-aging. Given that the median age of cancer diagnosis is 66 years and that immunotherapeutic interventions such as cancer vaccines are currently given in combination with or after other forms of treatments which themselves have immune-modulating potential such as surgery, chemotherapy and radiotherapy, the choice of adjuvants requires careful consideration in order to achieve the maximum immune response in a compromised environment. Moreover, it is now time to consider new forms of immune adjuvants alongside a holistic perspective which enables exercise, diet and phycology care to be part of the treatment. In this review, adjuvants will be discussed with respect to the above-mentioned important elements.